Is It Possible to End Female Circumcision in Africa? - Dunn, Fiona (Clinical Journal of Obstetrics and Gynecology, 2018)
Female genital mutilation / cutting remains a widespread practice throughout Africa. There has been a worldwide effort to do away with FMG/C, but tensions exist between those who aim to abolish FGM/C and those who desire to perpetuate the tradition. While many Western and African experts and organizations agree on the health risks and human rights concerns with FGM/C, others fear that Westerners are imposing their ideas and lack of cultural understanding, trying to eliminate a practice central to the identity of many Africans. The issue must be approached respectfully and collaboratively, with great effort on the part of Westerners to understand the cultural context and rationale of this tradition. Ultimately, if FGM/C is to be eradicated in the foreseeable future, whole African communities and international support agencies must be engaged and empowered to collectively evaluate the implications of the practice and accelerate its demise.